STRATEGI PEMBELAJARAN PENDIDIKAN JASMANI DI SEKOLAH DASAR INKLUSIF KOTA YOGYAKARTA - Taryatman Taryatman; Abdul Rahim (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to obtain the learning plan of the physical education in inclusive elementary schools, find out the learning process and identify physical education learning strategies in inclusive elementary schools in Yogyakarta city. The research method used is descriptive qualitative. The data collection techniques in this study employed direct field observation techniques during the learning process of Physical Education, direct interview towards theteachers of physical education and mentoring teachers, and documentation by collecting various images or data that support this research. The study was conducted in 3 elementary schools: 1) Taman Muda Ibu Pawiyatan, 2) SD Negeri Baciro and 3) SD Negeri Pakel. Data were collected through the techniques of direct observation, interviews, and documentation so that they can yield overview and conclusion regarding to the learning strategies. The results of the research showed that in the planning of physical learning, there should be more serious and better preparation regarding to the syllabus, lesson plans and assessment. In the process of learning physical education, the research result showed that some students with special needs for athletic sports, especially running subject does not need significant adjustment, however blind students and deaf students felt that they need some adjustment in the running subject. There are a number of physical learning strategies for students with special needs including the use of appropriate language, making task sequences, allocation of time for learning, modification of the games/ sports rules and learning environments.